Keberkesanan penyampaian kuliah menggunakan teknologi webcast dalam mod yang berbeza - Kasa, Zakaria; Md. Yunus, Aida Suraya; Asmuni, Azizan; Napis, Suhaimi; Abu Samah, Bahaman; Mohd Yusoff, Mohd Zul; Khanafie, Mohd Rizal; Abdul Wahab, Hasmah; Sayid Ismail, Tn. Sayid Mohammad Nazari (Universiti Putra Malaysia Press, 2006)
The applications of webcast technology are expanding in both the corporate and broadcasting sectors. However, the use of webcast technology in teaching has not been widely explored, especially in Malaysia. Thus, a study was conducted to determine the effectiveness of the webcast technology in teaching and learning institutions of higher education. In this experimental study, three modes of webcast delivery were exposed to the subjects. The modes were live streaming, prerecorded streaming and video-on-demand (VOD. Subjects in these three modes of delivery were considered as experimental groups, while subjects who followed face-to-face lecture were considered as control group. A set of questionnaires was distributed to subjects in order to obtain information on their perceptions towards the use of webcast technology. Pre-test was at first administered to gauge pre-experimental stage of subjects' academic capabilities. Then after the study, a post-test were conducted to determine whether there were significant difference in academic achievement of students who attended the different modes of webcast delivery. The findings showed that perceptions of subjects were moderate and positive towards the delivery modes using webcast technology, lecture method, learning materials used, and the facilities provided in the webcast modes of delivery. In terms of academic achievement, there was no significant difference between post-test and pre-test for all four modes of delivery. This implies that webcast modes of delivery have the potential to be used on a larger scale to the teaching and learning of both on-campus and off campus programmes.